A case of vesical leiomyoma and acute urinary obstruction. Issue 692 (June 1983) - Foster, M. E.; Rees, R. W.
Abstract : A case of acute urinary retention due to a vesical leiomyoma is described. This is an unusual presentation and the treatment is discussed.